The Benefit-Risk Balance of Nab-Paclitaxel in Metastatic Pancreatic Adenocarcinoma - Péron, Julien; Giai, Joris; Maucort-Boulch, Delphine; Buyse, Marc (Pancreas, 2019)
The benefit-risk balance of 5-fluorouracil, oxaliplatin, irinotecan, and leucovorin versus gemcitabine assessed using generalized pairwise comparison was strongly positive. We sought to assess the benefit-risk balance of nab-paclitaxel plus gemcitabine using the data of the MPACT trial, as it is an alternative to 5-fluorouracil, oxaliplatin, irinotecan, and leucovorin. This statistical method allows for the simultaneous analysis of several prioritized outcomes. The first priority outcome was survival time (overall survival). The second priority outcome was toxicity. The overall treatment effect was quantified using the overall net benefit. Multiple sensitivity analyses were performed to assess the consistency of the results according to possible patients' preferences. In this trial, 861 patients received nab-paclitaxel plus gemcitabine or gemcitabine alone. The overall net benefit favored strongly and significantly the combination group. When only large survival differences were considered clinically relevant, the net benefit was not in favor of the combination group. The overall net benefit is a clinically intuitive way of comparing patients with respect to all important efficacy and toxicity outcomes. The nab-paclitaxel plus gemcitabine combination has a positive benefit-risk balance, but it might not be suitable for patients who would consider losing several months of survival to avoid a significant toxic event.